Volume Matters in Ultrasound-Guided Perineural Dextrose Injection for Carpal Tunnel Syndrome: A Randomized, Double-Blinded, Three-Arm Trial - Lin, Meng-Ting; Liao, Chun-Li; Hsiao, Ming-Yen; Hsueh, Hsueh-Wen; Chao, Chi-Chao; Wu, Chueh-Hung (Frontiers in Pharmacology, 2020)
Ultrasound-guided perineural dextrose injection (PDI) has been reported effective for carpal tunnel syndrome (CTS). Higher volume of injectate may reduce adhesion of median nerve from other tissues, but volume-dependent effects of PDI in CTS remain unknown. We aimed to investigate whether PDI with different injectate volumes had different effects for CTS participants. In this randomized, double-blinded, three-arm trial, sixty-three wrists diagnosed with CTS were randomized into three groups that received ultrasound-guided PDI with either 1 mL, 2 mL or 4 mL of 5% dextrose water. Primary outcome as Visual Analog Scale (VAS) and secondary outcomes including Boston Carpal Tunnel Questionnaire (BCTQ), Disability of the Arm, Shoulder and Hand score (QuickDASH), electrophysiological studies and cross-sectional area (CSA) of the median nerve at carpal tunnel inlet were assessed before and after PDI at the 1st, 4th, 12th and 24th weeks. For within-group analysis, all three groups (21 participants, each) revealed significant improvement from baseline in VAS, BCTQ and QuickDASH at the 1st, 4th, 12th and 24th weeks. For between-group analysis, 4 mL-group yielded better VAS reduction at the 4th and 12th weeks as well as improvement of BCTQ and QuickDASH at the 1st, 4th, and 12th weeks, compared to other groups. No significant between-group differences were observed in electrophysiological studies or median nerve CSA at any follow-up time points. There were no severe complications in this trial, and transient minor adverse effects occurred equally in the three groups. Our clinical trial concluded ultrasound-guided PDI with 4 mL of 5% dextrose provided better efficacy than with 1 mL and 2 mL based on symptom relief and functional improvement for CTS, with no reports of severe adverse effects.